Asia Agrifood System’s 5 Linked Transformations - Reardon, Thomas (CGIAR Independent Science and Partnership Council, 2013)
This paper focuses on emerging evidence from surveys and broad trend information of the interrelated 5 transformations (urbanization; diet change; food market transformation: rural factor market transformation; agricultural technology and farm scale change). South Asia is the focus of the paper.